1986
DOI: 10.3133/ofr86455
|View full text |Cite
|
Sign up to set email alerts
|

Scattering and attenuation of high-frequency seismic waves; development of the theory of coda waves

Abstract: Coda waves are one of the most striking features recorded on seismograms, and their study has bloomed over the last 10 years. Scattering and attenuation of high-frequency seismic waves constitute key subjects in both theoretical and applied research in present-day seismology. However, the narrow relations among coda waves, scattering, and attenuation are not taken into account often enough, nor is an overall comprehension of these subjects always offered. Coda waves of local earthquakes can be considered as ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 200 publications
0
3
0
Order By: Relevance
“…Finally, it is interesting to note that the special features of coda waves have been widely used by seismologists to obtain magnitude-duration formulae for regional earthquakes (Bisztricsany 1958;Soloviev 1965;Tsumura 1967;Lee, Bennett & Meagher 1972), and to estimate seismic moment (Herrmann 1980;Singh & Herrmann 1983), spectral scaling laws of local earthquakes and local Q (Aki & Chouet 1975;Rautian & Khalturin 1978;Herrmann 1980). An excellent review of theoretical and observational results about coda waves can be found in Herraiz & Espinosa (1986).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is interesting to note that the special features of coda waves have been widely used by seismologists to obtain magnitude-duration formulae for regional earthquakes (Bisztricsany 1958;Soloviev 1965;Tsumura 1967;Lee, Bennett & Meagher 1972), and to estimate seismic moment (Herrmann 1980;Singh & Herrmann 1983), spectral scaling laws of local earthquakes and local Q (Aki & Chouet 1975;Rautian & Khalturin 1978;Herrmann 1980). An excellent review of theoretical and observational results about coda waves can be found in Herraiz & Espinosa (1986).…”
Section: Introductionmentioning
confidence: 99%
“…Generally the coda results from waves that sample the whole region between the source and the seismic array. It contains global information about the heterogeneous structures of the medium, yet neither the different seismic wave propagation mechanisms in heterogeneous media nor the wave type that compose the coda are fully understood [see Herraiz & Espinosa (1986) for a complete review]. The classical studies made to understand the coda are based on statistical analysis (Aki 1969; Aki & Chouet 1975; Kopnichev 1977; Sato 1977a,b; Gao et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Herrmann (1980) proved that the coda, as recorded on broad-band instruments, can also be used to estimate Q. A very complete summary about the state of the art has been written by Herraiz & Espinosa (1986). Q values are related to the attenuation rate of crustal phases (Herrmann 1980;Singh & Herrmann 1983) and to several geophysical parameters such as heat flow, electrical conductivity, seismic velocities and crustal thickness (Der & McElfresh 1977;Lachenbruch 1979;Singh & Herrmann 1983;Pujades et al 1990).…”
Section: Introductionmentioning
confidence: 99%